Dosimetric impact of amino acid positron emission tomography imaging for target delineation in radiation treatment planning for high-grade gliomas - Kazda, Tomas; Pafundi, Deanna H; Kraling, Alan; Bradley, Thomas; Lowe, Val J; Brinkmann, Debra H; Laack, Nadia N (Physics and imaging in radiation oncology, 2018)
BACKGROUND AND PURPOSE: The amino-acid positron emission tomography (PET) tracer 3,4-dihydroxy-6-[18F] fluoro-l-phenylalanine (18F-DOPA) has increased sensitivity for detecting regions of biologically aggressive tumors compared to T1 contrast-enhanced (T1-CE) magnetic resonance imaging (MRI). We performed dosimetric evaluation of treatment plans prepared with and without inclusion of 18F-DOPA-based biological target volume (BTV) evaluating its role in guiding radiotherapy of grade III/IV gliomas. MATERIALS AND METHODS: Eight patients (five T1-CE, three non-contrast-enhancing [NCE]) were included in our study. MRI only-guided anatomic plans and MRI+18FDOPA-PET-guided biologic plans were prepared for each patient, and dosimetric data for target volumes and organs at risk (OAR) were compared. High-dose BTV60Gy was defined as regions with tumor to normal brain (T/N) >2.0, while low-dose BTV51Gy was initially based on T/N >1.3, but refined per Nuclear Medicine expert. RESULTS: For T1-CE tumors, planning target volumes (PTV) were larger than MRI-only anatomic target volumes. Despite increases in size of both gross target volumes and PTV, with volumetric-modulated arc therapy planning, no increase of dose to OAR was observed while maintaining similar target dose coverage. For NCE tumors, MRI+18F-DOPA PET biologic imaging identified a sub-region of the large, T2-FLAIR abnormal signal which may allow a smaller volume to receive the high dose (60 Gy) radiation. CONCLUSIONS: For T1-CE tumors, PTVs were larger than MRI-only anatomic target volumes with no increase of dose to OARs. Therefore, MRI+18F-DOPA PET-based biologic treatment planning appears feasible in patients with high-grade gliomas.
Keywords: Amino acid PET; PET-guided radiation therapy; 18F-DOPA PET; Planning study